Absolute Magnitudes of Early-type Supergiants from uvbyβ Photometry and Parallax Data. (10th June 2020) - Kaltcheva, Nadia; Paunzen, Ernst; Prišegen, Michal; Golev, Valeri; Watson, Michael
Abstract: We combine Strömgren–Crawford uvbyβ photometry with Gaia-DR2 parallaxes for a sample of 880 supergiants of O-B9 spectral types to explore the potential of these data in providing physical parameters of such stars. We obtained reddening corrections and photometric absolute magnitudes via the existing uvbyβ calibrations. We calculated Gaia-based absolute magnitudes applying individual photometric reddening corrections for each star. The uvbyβ photometry is particularly useful in this case, since it provides color excess independent of spectral classification, thus overcoming possible MK classification inconsistencies. After evaluating and correcting the effect of luminosity class mis-classifications on the photometric absolute magnitudes, we found a reasonable agreement between the photometric and Gaia-based absolute magnitudes for this sample. At this point, the color–magnitude M V versus ( b − y )0 diagrams based on photometry and Gaia show slight discrepancies, which have to be addressed in the light of the next Gaia data releases. The derived precise reddening corrections should further help to refine the physical parameters of these stars and address their connection to OB-associations and regions of star formation.